COLCHICINE INHIBITION OF NERVE FIBER FORMATION IN VITRO - Daniels, Mathew P. (The Rockefeller University Press, 1972)
Inhibition of nerve fiber (neurite) formation by colchicine and Colcemid was studied in monolayer cultures of dissociated spinal ganglia of the chick. Replica cultures were fixed after appropriate incubation and alkaloid treatment. Quantitative estimates of the mean total neurite length per neuron (MNL) were made by use of camera lucida tracing. MNL values plotted against time of incubation gave control curves with an initial lag period, a phase of rapid increase, and a final phase in which MNL increase was retarded. Colchicine at 0.01–0.05 µg/ml (2.4 x 10(-8)-1.2 x 10(-7) M) caused reversible, concentration dependent, inhibition of the increase in MNL when applied during the lag period or phase of rapid increase. At the highest concentration there was a net decrease in MNL. The effect of Colcemid at 0.05 µg/ml was similar to that of colchicine, but more rapidly reversible. In most experiments there was no loss of neurons during the period of inhibition of MNL increase by colchicine or Colcemid. Therefore selective destruction of neurons was not involved in the inhibition of neurite growth. Prolonged incubation after treatment with the highest concentration used resulted in a 50% loss of neurons, in part through detachment of viable cells. Quantitative radioautography of the alkaloid-treated neurons with leucine-(14)C indicated little or no inhibition of incorporation into protein during inhibition of MNL increase. The results strongly suggest that inhibition of neurite growth involves a specific effect of colchicine, presumably the disruption of microtubules. They are thus consistent with the hypothesis that the polymerization of microtubules is essential to the formation of nerve fibers.